Upaya Meningkatkan Produktivitas Kerja Melalui Standarisasi Rekrutmen Karyawan Bank Muamalat KCU Makassar (Studi Penetapan Status Pernikahan) - Asmita Nur Amalia (Institut Agama Islam Negeri Palopo, 2021)
The purpose of this study is first to find out the description of determining marital status as a standard for employee recruitment at Bank Muamalat KCU Makassar, second to find out the reasons for implementing standardization of marriage at Bank Muamalat KCU Makassar, and third to find out the relationship between marital status in increasing employee work productivity at Bank Muamalat KCU Makassar. The research method used is a type of qualitative research, using a descriptive approach and an associative approach. The results of this study indicate that the determination of marital status as a standardization of recruitment at Bank Muamalat focuses on the Frontliners because Frontliners are the front guard who are the key to the good name and image of the company through excellent service. Excellent service is produced through employees who really focus on customer satisfaction and are not divided by personal problems, especially for people who are already married, where the problem level is considered to be far more complex than those who are not married.